2022
DOI: 10.1021/acs.chemmater.1c03813
|View full text |Cite
|
Sign up to set email alerts
|

Tough and Healable Elastomers via Dynamic Integrated Moiety Comprising Covalent and Noncovalent Interactions

Abstract: Elastomers that combined excellent mechanical performance and healability are essential to the advancement of stretchable electronics. However, the strength and toughness of healable elastomers tend to be mutually exclusive. Herein, a new strategy of the dynamic integrated moiety is developed to construct covalent and noncovalent cross-linked polyurethane (CNPU) elastomers. The covalent and noncovalent interactions synergistically enhance the overall mechanical properties of polyurethane elastomers such as ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Compared to extrusion 3D printing, VP-3DP is preferred to produce prints with high resolution and small feature size . Photoreactive resins for VP-3DP usually contain acrylated and methacrylated monomers and oligomers that undergo free radical polymerization and yield cross-linked thermosets. , During this process, the mobility and diffusion of the propagating chains change, and the composition and the distance in between cross-links vary throughout the network, and as a result, the 3D printed thermosets exhibit low toughness. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to extrusion 3D printing, VP-3DP is preferred to produce prints with high resolution and small feature size . Photoreactive resins for VP-3DP usually contain acrylated and methacrylated monomers and oligomers that undergo free radical polymerization and yield cross-linked thermosets. , During this process, the mobility and diffusion of the propagating chains change, and the composition and the distance in between cross-links vary throughout the network, and as a result, the 3D printed thermosets exhibit low toughness. , …”
Section: Introductionmentioning
confidence: 99%
“…3,4 During this process, the mobility and diffusion of the propagating chains change, and the composition and the distance in between cross-links vary throughout the network, and as a result, the 3D printed thermosets exhibit low toughness. 5,6 One of the main strategies to increase toughness in polymer networks is to include monomers and oligomers with sacrificial bonds to dissipate energy. 7−9 Because of their reversibility, noncovalent interactions can dissipate excess energy; increasing the mechanical strength of thermosets without sacrificing their elongation before failure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many current healable polymers are based on supramolecular reversible interaction, such as host–guest interaction, , metal–ligand coordination, ionic interaction, , and hydrogen bonding. , It has been revealed that supramolecular reversible interactions can effectively shorten the distance of the dynamic molecular segment, which favors a high healing ratio and efficient healing . For example, Kang and coworkers reported an efficient self-healing elastomer that can heal itself in 1.5 h through multistrength hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others, originating from the destruction and recombination of dynamic interactions, enable the repeated healing of polymer materials after being damaged. 16 Many current healable polymers are based on supramolecular reversible interaction, 17−21 such as host−guest interaction, 22,23 metal−ligand coordination, 24 ionic interaction, 25,26 and hydrogen bonding. 27,28 It has been revealed that supramolecular reversible interactions can effectively shorten the distance of the dynamic molecular segment, which favors a high healing ratio and efficient healing.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Una de ellas ha sido el desarrollo de materiales compuestos elastoméricos, donde la carga cumpla una doble función: reforzante y como agente reparador [6][7][8]. Otra estrategia que despierta gran interés es la combinación de diferentes mecanismos de reparación, creando redes duales entrecruzadas donde se combinan interacciones no-covalentes, enlaces covalentes, o ambos [3,[9][10][11][12][13]. Los sistemas no-covalentes se caracterizan por tener una baja energía de enlace en comparación con los sistemas covalentes puros, por lo que suelen tener mayores eficiencias de reparación ya que esto facilita la restauración de los enlaces rotos incluso a temperatura ambiente.…”
Section: Introductionunclassified